Lycorine Attenuates Airway Inflammation in an OVA induced Allergic Asthma Model - Wang, Yanbing; Wu, Yang; Alzahrani, Abdullah R.; Seshadri, Vidya Devanathadesikan; Li, Feng (Indian Journal of Pharmaceutical Education and Research, 2023)
Background: Asthma is one of the most prevalent, complex, and severe respiratory disorders, with rising rates of occurrence and death in both children and adults. An alkaloid derived from plants, lycorine possesses several pharmacological effects, primarily anti-inflammatory and antioxidative properties. Materials and Methods: In the current study, the anti-asthmatic potential of lycorine against ovalbumin (OVA)-induced asthma mice model has been examined. The animals were categorized into five groups. The group I mice received saline while the group II mice received OVA. Groups III mice were provided with OVA + Lycorine in low dose whereas group IV mice were given OVA + Lycorine in high dose. Group V animals received OVA + Dexamethasone, which was used as the positive control. The bronchoalveolar lavage fluid isolated from the lungs was utilized to estimate various parameters such as total and differential immune cells (eosinophils, neutrophils, lymphocytes, macrophages), secreted inflammatory cytokines levels, and oxidative stress markers. The lungs were subjected to histological examination and respiratory mechanics examination. Results: Lycorine treatment significantly suppressed the total and differential immune cells, IgE, IL-4, IL-5, IL-13, and TNF-α cytokines, MDA, NO2 and NO3 levels and enhanced the IFN-γ cytokine level along with the SOD, CAT, and GSH enzyme activities. Further, the histopathological study revealed that lycorine was able to decrease the thickness of the columnar epithelial cells in the airways. Thus, lycorine suppressed the ROS generation that in turn reduced the inflammation in the airways of the lungs by reducing Th2 cytokines and augmenting the levels of Th1 cells. Conclusion: These findings indicate that lycorine was able to regulate the Th1/Th2 balance OVA-challenged asthmatic mice, signifying its protective impact that may be valuable in the management of allergic asthma.
Keywords: Asthma; Ovalbumin; Lycorine; Inflammatory cytokines; Oxidative stress